2024
DOI: 10.21897/rmvz.2732
|View full text |Cite
|
Sign up to set email alerts
|

Efecto del amamantamiento restringido sobre características de crecimiento en ovinos de pelo colombiano

Abstract: Objetivo. Evaluar el efecto del amamantamiento restringido (AR) sobre parámetros de crecimiento (peso ajustado (PA) y ganancia de peso diaria (GPD), condición corporal (CC) y puntaje de FAMACHA® (FA) durante la lactancia y pos-destete en ovejas de pelo colombiano (OPC). Materiales y métodos. 76 OPC con crías, fueron asignados a uno de dos tratamientos. Tratamiento 1 (T1), corderos con amamantamiento continuo (AC): 24 horas con la madre (n= 38). Tratamiento 2 (T2), amamantamiento restringido (AR), 10 horas (n=3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 33 publications
(51 reference statements)
0
0
0
Order By: Relevance
“…The weaning weight presented here is higher than that reported in other studies: 11.6 ± 3.6 kg [ 3 ], 11.2 ± 3.7 kg [ 4 ], and 10.3 ±1.7 kg [ 5 ]. But less than the weight found by Palacios et al [ 2 ] (15.1 ± 3.9) and Lenis et al [ 12 ] (18.5 ± 0.7).…”
Section: Discussioncontrasting
confidence: 81%
See 4 more Smart Citations
“…The weaning weight presented here is higher than that reported in other studies: 11.6 ± 3.6 kg [ 3 ], 11.2 ± 3.7 kg [ 4 ], and 10.3 ±1.7 kg [ 5 ]. But less than the weight found by Palacios et al [ 2 ] (15.1 ± 3.9) and Lenis et al [ 12 ] (18.5 ± 0.7).…”
Section: Discussioncontrasting
confidence: 81%
“…Several studies have reported the behavior of growth variables in OPC lambs. The BW was lower than that presented by Montes-Vergara et al [ 3 ] (2.8 ± 0.21 kg), Vergara et al [ 4 ] (2.6 ± 0.6 kg), Palacios et al [ 2 ] (2.8 ± 0.8 kg), Noriega et al [ 5 ] (3.2 ± 0.5 kg), and Lenis et al [ 12 ] (3.10 ± 0.70 kg). These differences are associated with the number of lambs at birth [ 34 ], ewe age [ 35 , 36 ], the feeding management of the pregnant ewes during the last third of gestation [ 37 ], and the male used during the breeding season [ 3 ].…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations